Pendekatan Scientific Berbantuan Media Pembelajaran Puzzle dalam Meningkatkan Curiosity dan Kemampuan Analogi Mahasiswa pada Pembelajaran Ekonomi - Nur, Andi St. Aisyah; Ramli, Anwar; Inanna, Inanna (Universitas Negeri Makassar, 2021)
This research is based on real conditions in the field, namely the low curiosity and analogy ability of students at the University of Muhammadiyah Bone, Campus 3 Kahu, through economics learning, especially in the subject of Introduction to Economics II, Taxation on the Basics of Social Sciences which has not used a scientifically assisted approach. puzzle learning media in the learning process. This type of research uses quantitative research with the type of research design, namely Quasi Experimental Design with the type of